ARE ISLAMIC STOCKS SAFE-HAVEN ASSETS? DYNAMIC EVIDENCE FROM INDONESIA - Igo Febrianto; Nindytia Puspitasari Dalimunthe; Faila Shofa (Jurnal Ilmu Ekonomi dan Pembangunan, 2026)
This study examines whether Islamic stocks in Indonesia function as safe-haven assets during major global crises by analysing their dynamic correlation with the conventional market. Using the Dynamic Conditional Correlation–Generalized Autoregressive Conditional Heteroskedasticity (DCC–GARCH), this research evaluates time-varying correlations between the Jakarta Composite Index (IHSG) and several financial assets, namely the Indonesia Sharia Stock Index (ISSI), Jakarta Islamic Index (JII), gold, and the USD/IDR exchange rate across four crisis periods: the Taper Tantrum (2013–2014), the U.S.–China Trade War (2018–2020), the COVID-19 pandemic (2020–2021), and the Russia–Ukraine geopolitical crisis (2022–2023). The findings show that Islamic stocks exhibit persistent positive co-movement with the conventional market, indicating limited safe-haven properties despite their theoretical resilience, while gold price and USD/IDR display weak or negative correlations, confirming their roles as short-term safe-haven assets. This study contributes by demonstrating that safe-haven characteristics are dynamic and crisis-dependent, implying that Islamic stocks offer limited diversification benefits during systemic shocks compared to gold and exchange rate exposure.